Concentrations, Compositions, and Deposition Rates of Dissolved Nitrogen in Western China: Insights From Snow Records - An, Yanqing; Xu, Jianzhong; Liu, Yanmei; Li, Xiaofei; Zhao, Huabiao; Kang, Shichang (Frontiers in Environmental Science, 2022)
Atmospheric nitrogen deposition is an important contributor to global and regional nitrogen cycles and could be critical limit nutrient for remote area. In this study, nitrogen species compositions, deposition fluxes, and historical records in mountains of Western China, including the Tibetan Plateau, were determined from snowpit and ice core samples collected from mountain glaciers. The mean concentration of total dissolved nitrogen (TDN) in the snowpit samples was 12.6 µmol L−1 (8.0–17.8 µmol N L−1) and comprised of 59% ammonium nitrogen, 35% nitrate nitrogen, and ~6% dissolved organic nitrogen. The deposition of nitrogen species, except organic nitrogen (likely due to its low concentrations) varied seasonally in a similar way based on the records of snowpit profile. The mass concentration and composition of nitrogen species in the surface snow/ice samples varied monthly, mainly because of melting processes based on monthly collected surface snow/ice samples in one of the glaciers. During melting, the inorganic nitrogen content could be lost significantly, whereas the dissolved organic nitrogen concentration could be enriched because of microbial activity. For the historical records, the nitrogen deposition in mountain areas of Western China was increased after 1960s by about one time of that compared with 1900-1950 and was dominated by ammonium-N. From the snowpit data, we estimated the total dissolved nitrogen deposition flux at 0.56–1.3 (mean 0.88) kg ha−1 a−1 in mountain area of Western China. These results could improve our understanding of nitrogen deposition and cycle in the mountain areas of Western China.